2013
DOI: 10.3390/ijerph10020515
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Monitoring Interval on Data Measurement: An Analysis of Step Counts of University Students

Abstract: The pedometer is a widely used research tool for measuring the level and extent of physical activity (PA) within population subgroups. The sample used in this study was drawn from a population of university students to examine the influence of the monitoring interval and alternate starting days on step-count activity patterns. The study was part of a national project during 2008–2010. Eligible subjects (641) were selected from a sample of 906 university students. The students wore pedometers continuously for 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
3
6
0
1
Order By: Relevance
“…The data analysis included only records when the pedometer was worn for at least 10 h a day during at least 4 weekdays/school days and 2 weekend days. Monitoring of at least 4 weekdays and 2 weekend days is suitable for predicting weekly physical activity in children and young adults (31,32). Incomplete records of daily step counts or an omission of the age, body height and body weight variables constituted a reason for excluding 5.37% (n = 20) of daughters, 6.04% (n = 21) of sons, 1.97% (n = 7) of mothers, and 4.3% (n = 13) of fathers ( Table 1).…”
Section: Samplementioning
confidence: 99%
“…The data analysis included only records when the pedometer was worn for at least 10 h a day during at least 4 weekdays/school days and 2 weekend days. Monitoring of at least 4 weekdays and 2 weekend days is suitable for predicting weekly physical activity in children and young adults (31,32). Incomplete records of daily step counts or an omission of the age, body height and body weight variables constituted a reason for excluding 5.37% (n = 20) of daughters, 6.04% (n = 21) of sons, 1.97% (n = 7) of mothers, and 4.3% (n = 13) of fathers ( Table 1).…”
Section: Samplementioning
confidence: 99%
“…Similarly maximum oxygen usage during high intensity exercise was predicted using a linear regression model based on step counts and other related body composition measures [ 87 ]. Other studies examined the influence of monitoring interval and alternative starting days for step count interventions in order to reliably assess and predict the participants’ physical activity [ 31 , 88 ]. ANOVA, inter class correlation and linear regression methods were used to model the collected data.…”
Section: Resultsmentioning
confidence: 99%
“…ANOVA, inter class correlation and linear regression methods were used to model the collected data. One study reported that a minimum of four days need to be monitored starting from Sunday [ 31 ]. Another study [ 88 ] also claimed that four days were required for a pedometer based intervention, with different monitoring periods for different step count collecting devices.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous adult literature, at-risk groups have less day-to-day variability and require less days to represent their typical physical activity level than healthy groups. For example, 3–5 days (using an accelerometer) or 4–7 days (using a pedometer) are needed to measure the typical physical activity level for a healthy adult group [ 45 , 46 , 47 , 48 , 49 ]. A group of adults with a spinal cord injury only needed 2 days of activity monitoring to sufficiently represent their daily behavior [ 50 ].…”
Section: Discussionmentioning
confidence: 99%